The development and psychometric properties of Multidimensional Hardiness Inventory for Young Adults in Indonesia - Shierlen Octavia; Dewi Maulina; Salma Ghina Sakinah Safari; Isabella Sasqia Mulya (Konselor, 2021)
The need to have a capacity to remain hardy despite stress and adversity, particularly in young adult groups, is an essential thing to address. However, to our knowledge, reliable and valid scales to measure the construct is still lacking, particularly in Indonesia. Thus, it encourages the development and validation of the Multidimensional Hardiness Inventory for Young Adults (MHIYA) in Indonesia to measure this capacity. MHIYA was developed through a comprehensive review of literature and a content validity testing process. The data from 326 participants aged 18-40 years old were analyzed using confirmatory factor analyses with a structural equation modelling approach. The final validated MHIYA consists of 18 items loading on three dimensions: commitment, control, and challenge. Cronbach’s α ranged between 0.780 and 0.902 in each dimension indicating high internal consistency reliability for each dimension of the MHIYA. The result from item discrimination analysis indicates that all items in MHIYA could distinguish individuals with high and low levels of hardiness. Therefore, MHIYA is a valid and reliable scale for measuring hardiness among young adults in Indonesia.